Nanoemulsões de anfotericina B: desenvolvimento, caracterização e atividade leishmanicida - Araújo, Gabriela Muniz Felix (2013)
Leishmaniasis is one of the most neglected diseases in the world. Its most severe clinical form, called visceral, if left untreated, can be fatal. Conventional therapy is based on the use of pentavalent antimonials and includes amphotericin B (AmB) as a second choice drug. The micellar formulation of AmB, although effective, is associated acute and chronic toxicity. Commercially available lipid formulations emerged to overcome such drawbacks, but the high cost involved limits widespread use of these preparations. Nanosized drug delivery systems, such as nanoemulsions (NE), have proven ability to solubilize hydrophobic compounds, to improve absorption and bioavailability, to increase efficacy and to reduce toxicity of the encapsulated drug. NE become even more attractive because they are inexpensive and easily produced. The aim of this work was to develop NE to incorporate AmB. NE were made by sonication method, through a mixture of surfactants, Kolliphor HS 15 and Brij ® 52, with the oil isopropyl myristate. AmB was added directly to the samples under magnetic stirring, using acidic and basic solutions to solubilize the drug and for adjustment of final pH. All NE showed neutral pH, values of conductivity were consistent with oil in water systems, and isotropic behavior. NE presented spherical structures with negative zeta potential value, monomodal size distribution and average diameter of the droplets with drug ranged from 33 to 132nm. Thermal analysis showed that AmB was not able to modify the behavior of the system, possibly to be dispersed in the internal phase. With respect to preliminary stability tests, centrifugation caused precipitation of the drug, heat stress led to turbidity of samples and at the end of the freeze-thaw cycle all samples maintained their transparency. AmB-NE showed similar statistically antileishmanial activity to AmB micellar formulation, which enables those systems to further tests, to assess their toxicity and also prove its effectiveness on amastigotes, in order to offer them as an alternative for the treatment of visceral leishmaniasis.